A Comparative Study on Women's Betrayal In Jung Chang's Wild Swans and Atiq Rahimi's The Patience Stone - Muhammad Thoriqussuud; Fathur Rohim; Abu Fanani; Akhmad Syaikhu; Atiq Mohammad Romdlon (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
This study is comparing women’s betrayal in two novels, Wild Swans a novel by Jung Chang and the Patience Stone a novel by Atiq Rahimi. The fact that Chinese’ women and Afghan women’s share the common issue, that is patriarchal one, the former faces the superior communist party, whilst, the latter faces the Mullah, the influential spiritual leader. Then, the women’s betrayal is worthy of analysis. The word ‘betrayal’ turns out to have a positive connotation instead of a negative one as heard in everyday life. Using descriptive and dramatic method, the study finds that both women in both novels have similarities and differences in their betrayal seen from the way they speak as well as act. In the similarities, both women betray the powerful people and their husbands, whilst, the differences are that people in power refer to the political parties in Wild Swans, a novel by Jung Chang, to the Mullah, a religious leader in the Patience Stone, a novel by Atiq Rahimi besides the husband is loyal to the political party in Wild Swans and to the religious teaching in the Patience Stone. Eventually, comparing women’s betrayal is worth a study since their betrayal gives a new life concept that women should play important roles in society not just men.